Synthesis and Photophysical Properties of Hexaphenylbenzene–Pyrrolo[3,2-b]pyrroles - Stężycki, Rafał; Reger, David; Hoelzel, Helen; Jux, Norbert; Gryko, Daniel T. (Synlett, 2018)
Methods for the synthesis of pyrrolo[3,2-b]pyrroles containing hexaphenylbenzene moieties at the 2- and 5-positions or the 1- and 4-positions have been developed. It was shown that placing a hexaphenylbenzene moiety at the 2- and 5-positions requires a Diels–Alder reaction between an alkyne-substituted pyrrolopyrrole core and a 2,3,4,5-tetraphenylcyclopenta-2,4-dien-1-one. The resulting dyes show a strong blue fluorescence that was hypsochromically shifted by chlorination at the 3- and 6-positions. The overall conjugation between the hexaphenylbenzene moieties and the pyrrolopyrrole core is limited, as evident from their photophysical properties. The hexaphenylbenzene moieties attached to the pyrrolo[3,2-b]pyrrole core could not be transformed into hexa-peri-hexabenzocoronenes through intramolecular oxidative aromatic coupling.
Keywords: chromophores; pyrrolopyrroles; halogenation; multicomponent reaction; hexaphenylbenzene; fluorescence